Applicability and implication of the use of real time kinematic GNS for property surveys in the Philippines - Balicanta, Louie P.
Property Survey is the use of surveying techniques and procedures to obtain the location, size and shape of a land parcel that is owned or claimed by individual or group entities. It is both technical and legal in nature. Real Time Kinematic (RTK) Global Navigation Satellite System (GNSS) method is the use of dual-frequency GNSS to obtain the position of an object/ entity in real time. Presently, this is widely used in the conduct of surveying tasks such as topographic surveys and stake-out activities in construction surveying. Its use in property survey is not a straightforward application and must consider different situations, problems and limitations. Factors to consider includes coordinate systems used in the country, concepts of common point, azimuths and distances, and limitations such as multipath and obstructions. Methodologies and tests include azimuth determination, survey under tree canopy and use for old and new surveys. The results of the experiments show that RTK-GNSS is applicable for parcel corner position determination with consideration to limitations such as obstructions, level of accuracy, systematic error from projection, different coordinate systems used in the country and poor identification of common points.
Keywords: Global Positioning System; Real Time Kinematic - Global Navigation Satellite System (RTK-GNSS).; Rapid static GNSS; Property survey; PRS92.; Technical descriptions